Understanding the future of lithium: Part 2, temporally and spatially resolved life‐cycle assessment modeling. (7th October 2019) - Ambrose, Hanjiro; Kendall, Alissa
Abstract: An array of emerging technologies, from electric vehicles to renewable energy systems, relies on large‐format lithium ion batteries (LIBs). LIBs are a critical enabler of clean energy technologies commonly associated with air pollution and greenhouse gas mitigation strategies. However, LIBs require lithium, and expanding the supply of lithium requires new lithium production capacity, which, in turn, changes the environmental impacts associated with lithium production since different resource types and ore qualities will be exploited. A question of interest is whether this will lead to significant changes in the environmental impacts of primary lithium over time. Part one of this two‐part article series describes the development of a novel resource production model that predicts future lithium demand and production characteristics (e.g., timing, location, and ore type). In this article, part two, the forecast is coupled with anticipatory life‐cycle assessment (LCA) modeling to estimate the environmental impacts of producing battery‐grade lithium carbonate equivalent (LCE) each year between 2018 and 2100. The result is a normalized life‐cycle impact intensity for LCE that reflects the changing resource type, quantity, and region of production. Sustained growth in lithium demands through 2100 necessitates extraction of lower grade resources and mineral deposits, especially after 2050. Despite the reliance on lower grade resources and differences in impact intensity for LCE production from each deposit, the LCA results show only small to modest increases in impact, for example, carbon intensity increases from 3.2 kg CO2 e/kg LCE in 2020 to 3.3 kg CO2 e/kg LCE in 2100.